A pharmacological assessment of agonists and modulators at α4β2γ2 and α4β2δ GABAA receptors: The challenge in comparing apples with oranges. (September 2016) - Ahring, Philip K.; Bang, Line H.; Jensen, Marianne L.; Strøbæk, Dorte; Hartiadi, Leonny Y.; Chebib, Mary; Absalom, Nathan
Graphical abstract: Abstract: Extrasynaptically located γ-aminobutyric acid (GABA) receptors type A are often characterized by the presence of a δ subunit in the receptor complex. δ-Containing receptors respond to low ambient concentrations of GABA, or respond to spillover of GABA from the synapse, and give rise to tonic inhibitory currents. In certain brain regions, e.g. thalamocortical neurons, tonic inhibition is estimated to represent the majority of total GABA-mediated inhibition, which has raised substantial interest in extrasynaptic receptors as potential drug targets. Thalamocortical neurons typically express α4β2/3δ receptors, however, these have proven difficult to study in recombinant in vitro expression systems due to the inherently low current levels elicited in response to GABA. In this study, we sought to characterize a range of agonists and positive allosteric modulators at α4β2δ and α4β2γ2 receptors. All tested agonists (GABA, THIP, muscimol, and taurine) displayed between 8 and 22 fold increase in potency at the α4β2δ receptor. In contrast, modulatory potencies of steroids (allopregnanolone, THDOC and alfaxalone), anesthetics (etomidate, pentobarbital) andD elta-S elective agents 1 and 2 (DS1 and DS2) were similar at α4β2δ and α4β2γ2 receptors. When evaluating modulatory efficacies, the neurosteroids and anesthetics displayed highest efficacy at α4β2γ2 receptors whereas DS1 and in particular DS2 had highest efficacy at α4β2δ receptors. Overall, several key messages emerged: (i) none of the tested compounds displayed significant selectivity and a great need for identifying new δ-selective compounds remains; (ii) α4β2δ and α4β2γ2 receptors have such divergent intrinsic activation properties that valid comparisons of modulator efficacies are at best challenging.